Control interno a los procesos de producción de la caja de banano para exportación y su relación con la rentabilidad de la empresa agrícola bananera Lucila, cantón La Maná, año 2013 - Vaca Vaca, Olga Cecilia (2015)
The acting evaluations give the proprietors of the companies and their administrators the opportunity to revise the goals and expectations. All the activities that are developed in the productive process of the entity, evidencing the application of the group of norms and administrative politicians that allow to the institution to optimize their economic resources and technicians. The goals proposed in the productive process of the country property, they have been completed in an efficient way, according to the manager's approach in the interview. The System of internal control means all the politicians and procedures adapted by the administration of an entity to help to achieve its objectives towards this to look for the orderly and efficient conduction of its business. Once evaluated the system of internal control of conformity to the pattern SEWS II, in which 8 components settle down, it was obtained 38.66% of control risk and 61.34% of level of trust, demonstrating the execution of the norms, political and procedures in the production process. The evaluation of the carried out internal control, allowed to identify the group of norms and political that were applied during the agricultural production. The system of control of production costs takes us to determine the weaknesses or falencias in the handling of costs, what is reflected in a decrease of the same ones and in the increment of the utilities. The financial states that it presents the company indicate the level of use of the financial resources that possesses and to those that consents the evaluated company, being demonstrated with the applied financial indicators.